TEACHERS’ OPINION ABOUT THE PROBLEMS OF IMPLEMENTATION OF PHYSICAL EDUCATION IN SECONDARY SCHOOL (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the results of a survey of the teachers of physical education. The analysisrevealed a number of problems hindering the implementation of physical education in the general24education of the Republic of Armenia and the effective teaching of "Physical Culture" schoolsubjectThe problem. Currently, the negative dynamics of the health status, insufficient level ofphysical fitness, lack of interest and stable motivation for systematic physical training of schoolagechildren are observed, from primary to high school. In this case, school physical education,with its main component of “Physical Culture”, is aimed to overcome the abovementionedproblems. However, the effective implementation of this process is hampered by a number ofissues.
Keywords: General education, physical education, school subject “Physical culture”, problems.